Conferencia: "Phase diagram of magnetic nanoparticles ensembles from Monte Carlo simulations in the framework of an effective macro spin model." - Russier, Vincent (My University, 2018)
In this presentation, after a brief overview of the topic we present Monte Carlo simulations aimed at model an actual experimental situation, namely the magnetic phases of well ordered superlattices made of either Co or Fe2O3. The model considered is the simplest effective macro-spin model, namely a monodisperse ensemble of dipolar hard spheres located on the nodes of a fcc lattice, with uniaxial MAE. We focus on the characterization of the low temperature phase of the system and consequently on the conditions under which the SFM can be obtained in the framework of the finite size scaling. The results are discussed with respect to the the disorder control variable which is either the amplitude of the MAE or the variance of the easy axes orientational distribution.
Conferencia
Keywords: Método de Monte Carlo; Metales